Effect of electromyostimulation training on muscle strength and sports performance - Seyri, K.; Maffiuletti, N. A. (Strength and Conditioning Journal, 2011)
Electrostimulation (EMS) is a widely use methodology in applied sports science. In contrast to a typical voluntary contraction initiated by the central nervous system (e.g., in resistance training), EMS involves involuntary contractions elicited by electrical current applied to the muscle. The effectiveness of this technique has been evaluated in numerous studies examining strength and physical performance. Other repors comparing short-term (i.e., <=3 weeks) and long-term (i.e., >=12 weeks) EMS application have also reported differential results. This article will review research examining the effect of EMS on increasing strength and power, especially in sports performance.